PENGEMBANGAN MEDIA QUESTION CARD ANATOMI (QUCARA) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Hildatut Tillawati; Julianto; Ayu Maghfirah Widiyati; Wasilatur Rahmah Siftia Rusydi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
Critical thinking skills are very important in primary education, but the limitations of concrete and interactive learning media remain an obstacle, especially in teaching material on the human respiratory system. This study aims to develop QUCARA (Question Card Anatomi) media that is proven to be valid, effective, and practical in supporting the improvement of critical thinking skills in fifth-grade elementary school students, by applying the ADDIE development research model involving 16 fifth-grade students at SDN Montok 1. Data were collected through validation sheets, pretest-posttest assessments, and teacher and student questionnaires, then analysed based on validity, effectiveness using N-Gain, and practicality. The validation results showed a score of 92% (Highly Valid). The effectiveness test demonstrated a significant increase from an average pretest score of 13.69% to a posttest score of 92.81%, with an N-Gain score of 91.67% (Highly Effective). The practicality of the media received a 100% response from teachers and 98.88% from students, resulting in an average media practicality rating of 99.44% (Very Practical). Thus, QUCARA media has been proven to be valid, effective, and practical in supporting the improvement of critical thinking skills in primary school students.